Prevalence of scoliosis among high school students - Wimonrat Sakullertphasuk (2018)
© 2015, Medical Association of Thailand. All rights reserved. Objective: This study aimed to survey the prevalence of scoliosis in Thai high school students. Material and Method: Physical therapists assessed the postural alignment in three planes during standing position by observation, palpation, and Adam’s forward bending test. The data were analyzed using descriptive statistics and Chi-square analysis. Results: Three hundred and seventy-four high school students (297 males and 77 females) were recruited from three schools in the Bangkok Metropolitan Area. The prevalence of scoliosis was 22.7%. A significant difference was observed between sex and scoliosis prevalence (χ2 = 6.73, p<0.05) with a prevalence ratio (female:male) of 1.70. A significant difference of scoliosis prevalence was found between school 1 and school 3 (χ2 = 4.33, p<0.05) with a ratio of 1.74. Most scoliosis levels were found at the thoracolumbar level. The assessments of 84.7% for waist form, 76.5% for scapular border, and 71.8% for thoracic scoliosis were the most common anomaly of postural alignment in the scoliosis group. Conclusion: The prevalence of scoliosis in females was higher than in males at a ratio of 1.70. A significant difference was revealed among schools that might be affected by environmental factors.